2021
DOI: 10.1007/s11356-021-17315-7
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and translocation of eight trace metals by the different tissues of Abelmoschus esculentus Moench. irrigated with untreated wastewater

Abstract: Usage of wastewater to irrigate crops increases in Egypt and the whole world as a result of water shortage. This study is conducted to explore the potential of Abelmoschus esculentus Moench. (Okra plant) to accumulate and translocate eight trace metals: lead: Pb, cadmium: Cd, chromium: Cr, copper: Cu, iron: Fe, manganese: Mn, nickel: Ni and zinc: Zn in its different tissues due to irrigation with untreated industrial wastewater. It extended to assess the effect of the irrigation with wastewater on the growth p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…Heavy metals' impact on CO 2 assimilation, either by reducing the activity of the carboxylase enzyme or by reducing the ATP and reductant pool, maybe the cause of the decline in photosynthetic pigments (Singh et al 2016). The same finding was made in Pisum sativum, Abelmoschus esculentus, and Japanese mustard spinach (Galal et al 2021;Ahmed et al 2022). (Abul Kashem and Kawai 2007).…”
Section: Photosynthetic Pigmentssupporting
confidence: 65%
See 4 more Smart Citations
“…Heavy metals' impact on CO 2 assimilation, either by reducing the activity of the carboxylase enzyme or by reducing the ATP and reductant pool, maybe the cause of the decline in photosynthetic pigments (Singh et al 2016). The same finding was made in Pisum sativum, Abelmoschus esculentus, and Japanese mustard spinach (Galal et al 2021;Ahmed et al 2022). (Abul Kashem and Kawai 2007).…”
Section: Photosynthetic Pigmentssupporting
confidence: 65%
“…Additionally, untreated wastewater has high TM concentrations, which contaminates the soil and, as a result, the crops grown in areas that use it for irrigation (Gatta et al 2015). Galal and Shehata (2015), Farahat et al (2017), Ahmed (2020), andAhmed et al (2022) reported the same results.…”
Section: Soil and Water Charactersmentioning
confidence: 75%
See 3 more Smart Citations